Comparison on losses and flux distribution between two of 3 phase distribution transformer 1000kVA assembled with regular and irregular stack of transformer core lamination - Ismail, Daut; Dina Maizana, Maiz Ahmad; Shuhaimi, Zakaria; S. Uthman; Soib, Taib (The Malaysian Research Group (MRG), 2008)
Organized by The Malaysian Research Group (MRG), 19th - 21st December 2007 at University of Salford, United Kingdom.